Jujuboside B Inhibits the Proliferation of Breast Cancer Cell Lines by Inducing Apoptosis and Autophagy - Guo, Lin; Liang, Yupei; Wang, Shiwen; Li, Lihui; Cai, Lili; Heng, Yongqing; Yang, Jing; Jin, Xing; Zhang, Junqian; Yuan, Shuying; Xu, Tong; Jia, Lijun (Frontiers in Pharmacology, 2021)
Jujuboside B (JB) is one of the main biologically active ingredients extracted from Zizyphi Spinosi Semen (ZSS), a widely used traditional Chinese medicine for the treatment of insomnia and anxiety. Breast cancer is the most common cancer and the second leading cause of cancer-related death in women worldwide. The purpose of this study was to examine whether JB could prevent breast cancer and its underlying mechanism. Firstly, we reported that JB induced apoptosis and autophagy in MDA-MB-231 and MCF-7 human breast cancer cell lines. Further mechanistic studies revealed that JB-induced apoptosis was mediated by NOXA in both two cell lines. Moreover, AMPK signaling pathway plays an important role in JB-induced autophagy in MCF-7. To confirm the anti-breast cancer effect of JB, the interaction of JB-induced apoptosis and autophagy was investigated by both pharmacological and genetic approach. Results indicated that autophagy played a pro-survival role to attenuate apoptosis. Further in vivo study showed that JB significantly suppressed the growth of MDA-MB-231 and MCF-7 xenografts. In conclusion, our findings indicate that JB exerts its anti-breast cancer effect in an association with the induction of apoptosis and autophagy.